The Ternary Structure of the Double-headed Arrowhead Protease Inhibitor API-A Complexed with Two Trypsins Reveals a Novel Reactive Site Conformation - Bao, Rui (American Society for Biochemistry and Molecular Biology, 2009)
The double-headed arrowhead protease inhibitors API-A and -B from the tubers of Sagittaria sagittifolia (Linn) feature two distinct reactive sites, unlike other members of their family. Although the two inhibitors have been extensively characterized, the identities of the two P1 residues in both API-A and -B remain controversial. The crystal structure of a ternary complex at 2.48 Å resolution revealed that the two trypsins bind on opposite sides of API-A and are 34 Å apart. The overall fold of API-A belongs to the β-trefoil fold and resembles that of the soybean Kunitz-type trypsin inhibitors. The two P1 residues were unambiguously assigned as Leu(87) and Lys(145), and their identities were further confirmed by site-directed mutagenesis. Reactive site 1, composed of residues P5 Met(83) to P5′ Ala(92), adopts a novel conformation with the Leu(87) completely embedded in the S1 pocket even though it is an unfavorable P1 residue for trypsin. Reactive site 2, consisting of residues P5 Cys(141) to P5′ Glu(150), binds trypsin in the classic mode by employing a two-disulfide-bonded loop. Analysis of the two binding interfaces sheds light on atomic details of the inhibitor specificity and also promises potential improvements in enzyme activity by engineering of the reactive sites.